Instruments Measuring Blunted Affect in Schizophrenia: A Systematic Review - Kilian, Sanja; Asmal, Laila; Goosen, Anneke; Chiliza, Bonginkosi; Phahladira, Lebogang; Emsley, Robin (PLOS ONE, 2015)
Blunted affect, also referred to as emotional blunting, is a prominent symptom of schizophrenia. Patients with blunted affect have difficulty in expressing their emotions. The work of Abrams and Taylor and their development of the Rating Scale for Emotional Blunting in the late 1970’s was an early indicator that blunted affect could indeed be assessed reliably. Since then, several new instruments assessing negative symptoms with subscales measuring blunted affect have been developed. In light of this, we aim to provide researchers and clinicians with a systematic review of the different instruments used to assess blunted affect by providing a comparison of the type, characteristics, administration and psychometric properties of these instruments. Studies reporting on the psychometric properties of instruments assessing blunted affect in patients with schizophrenia were included. Reviews and case studies were excluded. We reviewed 30 full-text articles and included 15 articles and 10 instruments in this systematic review. On average the instruments take 15–30 minutes to administer. We found that blunted affect items common across all instruments assess: gestures, facial expressions and vocal expressions. The CAINS Self-report Expression Subscale, had a low internal consistency score. This suggests that this sub-scale does not reliably assess patients’ self-reported blunted affect symptoms and is likely due to the nature of blunted affect. Instruments correlated minimally with instruments measuring positive symptoms and more importantly with depression suggesting that the instruments distinguish between seemingly similar symptoms.